Evaluation of drought stress at vegetative growth stage on the grain yield formation and some physiological traits as well as fluorescence parameters of different bread wheat cultivars - Saeidi, Mohsen; Ardalani, Shiva; Jalali-Honarmand, Saeid; Ghobadi, Mohammad-Eghbal; Abdoli, Majid (Acta Biologica Szegediensis, 2015)
The effects of water stress on grain yield, its components, and physiological traits during the vegetative stage of wheat have been evaluated. Greenhouse trials were carried out by using factorial experiment based on randomized complete block design (RCBD) in three replications. Moisture stress was applied at vegetative growth stage (soil moisture was around 50% of field capacity from the beginning of stem elongation to flowering stage) and different wheat cultivars (such as Pishtaz, DN-11, Sivand and Marvdasht) were evaluated as the second factor. Water stress significantly decreased grain yield by decreasing the number of grains per spike. Under water stress from the beginning of stem elongation to flowering stages, Sivand and DN-11 cultivars had the lowest grain yield. The lowest and the highest reductions in grain yield and biological yield were detected in Marvdasht and DN-11, respectively. Results show that Marvdasht had the highest, while DN-11 had the lowest relative water constant (RWC) and performance index (PI) values. Water stress significantly decreased the chlorophyll content, PI and RWC values, at the same time significantly increased the carotenoid concentration, whereas the maximum quantum yield of photosystem II (Fv/Fm) did not change. According to the results, Pishtaz and Marvdasht cultivars are tolerant against drought stress and can recover very fast after stress is eliminated.